Effect of the Covid-19 Pandemic on Firm Value with Profitability as Moderation - Andrian Januar Ramadhan; Taufiq Hidayat (IDEAS: Journal of Management & Technology, 2022)
This study examines the effect of the COVID-19 pandemic on firm value with profitability as a moderator. This study was conducted on companies that are included in the LQ45 index in the 2017-2020 period. This study used a purposive sampling method so that 26 companies were included in the LQ45 index with 106 observations. For this relationship, firm value was proxied using Price to Book Value (PBV) and profitability variable was proxied using Return on assets (ROA). The results of the study show that the COVID-19 pandemic has a negative effect on firm value. ROA as a moderator weakens the negative impact of the COVID-19 pandemic.